Glutamate forward and reverse transport: From molecular mechanism to transporter-mediated release after ischemia - Grewer, Christof (2008)
Glutamate transporters remove the excitatory neurotransmitter glutamate from the extracellular space after neurotransmission is complete, by taking glutamate up into neurons and glia cells. As thermodynamic machines, these transporters can also run in reverse, releasing glutamate into the extracellular space. Because glutamate is excitotoxic, this transporter-mediated release is detrimental to the health of neurons and axons, and it, thus, contributes to the brain damage that typically follows a stroke. This review highlights current ideas about the molecular mechanisms underlying glutamate uptake and glutamate reverse transport. It also discusses the implications of transporter-mediated glutamate release for cellular function under physiological and patho-physiological conditions.